Pengaruh Price dan Experiential Marketing Terhadap Revisit Intention Melalui Customer Satisfaction Sebagai Variabel Intervening Pada Customer Puninoth Studio Self Photo Studio Semarang - Nurhastuti, Ellinda Febrilia; Prabowo , Heri; Indiworo, Rr. Hawik Ervina (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2024)
This study aims to investigate the effect of price and experiential marketing on revisit intention through customer satisfaction as an intervening variable in Puninoth Studio Self Photo Studio Semarang. The research method used in this study is quantitative method. The population in this study is visitors to Puninoth Studio Semarang and the sample that has been determined in this study is 138 customers. This study used SmartPLS software to answer the main facts with data collection carried out through surveys by distributing questionnaires. The results of the research hypothesis test show that Price and Experiential Marketing have a positive and significant effect on Customer Satisfaction. Customer Satisfaction has a positive and significant effect on Revisit Intention. Price and Experiential Marketing do not affect Revisit Intention but Price and Experiential Marketing affect Revisit Intention through Customer Satisfaction mediation. The results of this study are expected to provide a better understanding of the factors that influence customers' revisit intentions in the photography industry and at the same time provide guidance for Puninoth Studio to improve their marketing strategies. The findings from this study can be a significant contribution in the context of business development in the photography industry.